Combining association mapping and transcriptomics identify HD2B histone deacetylase as a genetic factor associated with seed dormancy in Arabidopsis thaliana. (4th April 2013) - Yano, Ryoichi; Takebayashi, Yumiko; Nambara, Eiji; Kamiya, Yuji; Seo, Mitsunori
Summary Seed dormancy is an important adaptive trait that enables germination at the proper time, thereby ensuring plant survival after germination. In Arabidopsis, considerable variation exists in the degree of seed dormancy among wild‐type accessions (ecotypes). In this paper, we identify a plant‐specific HD2 histone deacetylase gene, HD2B (At5g22650), as a genetic factor associated with seed dormancy. First, genome‐wide association mapping of 113 accessions was used to identify single nucleotide polymorphisms that possibly explain natural variation for seed dormancy. Integration of genome‐wide association mapping and transcriptome analysis during cold‐induced dormancy cycling identified HD2B as the most plausible candidate gene, and quantitative RT‐PCR analysis demonstrated that HD2B expression was up‐regulated by cold and after‐ripening (dry storage of mature seed), treatments that are known to break seed dormancy. Interestingly, quantitative RT‐PCR analysis in 106 accessions revealed that the expression of HD2B in imbibed seeds was significantly suppressed in most of the dormant accessions compared with less‐dormant accessions, suggesting that suppression of HD2B expression may be important to maintain seed dormancy in dormant accessions. In addition, transgenic seeds of a dormant Cvi‐0 accession that carried a 2.5 kb genomic DNA fragment of HD2B cloned from a less‐dormant Col‐0 accession (ColHD2B/Cvi‐0) exhibited reduced seed dormancy accompanied by enhanced expression of HD2B when after‐ripened or cold‐imbibed. Endogenous levels of gibberellin were found to be increased in the imbibed seeds of after‐ripened ColHD2B/Cvi‐0 compared with wild‐type Cvi‐0. These results suggest that HD2B plays a role in seed dormancy and/or germinability in Arabidopsis thaliana.